The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1590/s1415-65551998000200003
|View full text |Cite
|
Sign up to set email alerts
|

Continuidade da ação internacional, características da empresa e obstáculos percebidos: um estudo na indústria brasileira de calçados

Abstract: O estudo teve como objetivo testar a existência de relação entre a percepção prévia de barreiras à exportação e a continuidade das empresas na atividade exportadora. Além disso, procurou verificar se determinadas características das empresas estão associadas a sua permanência na atividade. Foram utilizados dados secundários constantes de um arquivo de dados sobre empresas exportadoras do COPPEAD/UFRJ, relativo a uma survey realizada em 1978 junto a 114 empresas brasileiras do setor calçadista. Entre os dados c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…An explanation for the lack of support for this relationship in Brazil might be that international managers in this country perceive external barriers as more relevant for inhibiting internationalisation than internal barriers due to environmental characteristics which are different from Chile. For example, firm size is larger in the Brazilian sample than the Chilean sample, and although size is not found to be a significant control variable in the model, previous studies have found that firm size is positively correlated with internationalisation performance in Brazil (De Carvalho and Da Rocha, 1998). Also, Azzi da Silva and da Rocha (2001) also found that, for Brazilian exporters, most barriers mentioned were related to the external environment.…”
Section: Discussionmentioning
confidence: 60%
“…An explanation for the lack of support for this relationship in Brazil might be that international managers in this country perceive external barriers as more relevant for inhibiting internationalisation than internal barriers due to environmental characteristics which are different from Chile. For example, firm size is larger in the Brazilian sample than the Chilean sample, and although size is not found to be a significant control variable in the model, previous studies have found that firm size is positively correlated with internationalisation performance in Brazil (De Carvalho and Da Rocha, 1998). Also, Azzi da Silva and da Rocha (2001) also found that, for Brazilian exporters, most barriers mentioned were related to the external environment.…”
Section: Discussionmentioning
confidence: 60%
“…Their findings suggest that firm size can be associated to some obstacles perceived by managers, but not to all of them. Previous Brazilian research also showed that the perception of barriers appeared to be correlated, at least to some extent, to firm size (Cardoso, 1980;Figueiredo and Almeida, 1988;De Carvalho and Da Rocha, 1998). Yet a study in the engineering services industry (Fleury, 1986) showed no relationship between these variables, which can be explained by the type of industry surveyed (a services industry).…”
Section: Firm Sizementioning
confidence: 77%
“…This obstacle, rated as number four in the present study, also appears in the same position in Cardoso's (1980) study and as the ninth obstacle in importance in Figueiredo and Almeida's (1988) study. De Carvalho and Da Rocha (1998) found that the perception of this obstacle systematically differentiated exporters and ex-exporters in the footwear industry, with ex-exporters more often seeing this obstacle as more important.…”
Section: High Transportation and Insurance Costsmentioning
confidence: 95%
See 1 more Smart Citation
“…Na mesma direção, Carvalho e Da Rocha (1998), tendo como ponto de partida três anos de análise(1980, 1990 e 1994), encontraram que, apesar das características da firma não terem poder explicativo nos anos de 1980 e 1990, em 1994, a variável com maior poder discriminante foi o tamanho da firma. O que se observou foi que as empresas que continuaram a exportar em tal ano tinham o dobro do tamanho daquelas que deixaram de exportar:Observando-se os dados relativos aos três períodos, verifica-se que a diferença entre o tamanho das exportadoras e das ex-exportadoras se vai tornando maior em 1980, 1990 e 1994, sucessivamente, sugerindo que as empresas menores abandonam mais facilmente a exportação ou fracassam na atividade ao longo do tempo (CARVALHO;. DA ROCHA, 1998, p. 34) De qualquer modo, apesar do grande interesse pelos teóricos do comportamento exportador, ainda não se conseguiu chegar a um consenso a respeito do impacto do tamanho da firma no desempenho exportador das organizações Figueiredo (1980).…”
unclassified